Factors Influencing Attitude Towards User's Attitude Towards Agency-Level Financial Application System (SAKTI) at the Directorate General of Highways (DJBM) with Gender as A Moderating Variable - Nugroho, Dendhi Agung; Baridwan, Zaki; Amirya, Mirna (Jurnal Locus Penelitian dan Pengabdian, 2025)
The implementation system's accuracy and the user's perception of technology are contingent upon the quality of the finance sector's report. Conducting research This objective is to examine the impact of Perceived Usefulness, Perceived Ease of Use, Perceived IT Beliefs, and Task-Technology Fit on the attitude towards the use of the System Application Agency Level Finance (SAKTI) application, with a variable Gender Moderatio. Conducting research This quantitative method survey was conducted on 146 personnel of the Directorate General of Highways who are active SAKTI users. PLS-SEM was implemented to conduct data analysis. The findings indicate that the attitude towards utilising the SAKTI application is significantly influenced by perceived IT beliefs and task-technology fit, while perceived usefulness and ease of use do not exhibit a significant impact. The gender variable has not been demonstrated to serve as a moderator in the relationship between the attitudes of users and their perceptions of the application. Results This affirms the significance of technology and its compatibility with the mission. Participate in the enhancement of public awareness of the reception system. Conducting research This provides a strategic recommendation. In order to enhance the implementation of SAKTI, training, alignment assignments, and user-centred approaches are implemented.